An Additivity Rule for the Vapor Pressure Lowering of Aqueous Solutions - Robinson, R. A. (J Res Natl Bur Stand A Phys Chem, 1965)
The question is discussed whether, and to what extent, the vapor pressure lowering of an aqueous solution containing two salts A and B can be compounded additively from the vapor pressure lowerings of a solution containing the salt A alone and another solution containing the salt B alone. In some instances the additivity of vapor pressure lowering is true within less than 0.5 percent; six systems have been examined and the greatest deviation from additivity amounts to 2.0 percent.